Why dialect and region matter: the aesthetic effects of the defamiliarization techniques of Blossoms and its readers’ reception - Sijia Yu (Cogent Arts & Humanities)
After Blossoms (《繁花》) won the Mao Dun Literature Prize, there were two prominent voices among readers. Some readers believed that using Shanghai dialect, a presentative of Wu Chiese, created noticeable regional characteristics and artistic charm in Blossoms. Another group of readers expressed that the dialect text of Blossoms was obscure in language and trivial in structure, so it was low in aesthetic value. These two voices reflected the primary responses of the Blossoms readers. Textual analysis reveals that using defamiliarization techniques in the form of local knowledge is the main reason for this phenomenon. Defamiliarization theory can explain the way Blossoms describes the urban experience in Shanghai and the aesthetic effects it produces. In contrast, reception theory can respond to the reasons for the divergence in the aesthetic preferences of the readers. This study provides a framework for understanding the creation and reception of dialect and regional literature.